Security, privacy and interoperability requirements for peruvian remote digital signatures - Papa Quiroz, Erik Alex (2021)
ABSTRACT There are several technological solutions currently available in the market that allow customers/citizens to digitally sign electronic documents through their smartphones. Regardless of how user-friendly they are, most of these platforms use proprietary schemes designed for particular use cases, which could not necessarily be applied to open, interoperable scenarios and where there could be legal consequences. To establish a general framework that may provide manufacturers with minimum safety, reliability, and legal requirements, several international organizations have proposed standards for both manufacturers and potential users. Within this context, this paper presents, for the first time in Peru, a list of security, privacy, and interoperability requirements for remote digital signature for the Peruvian state. This research was based on features of the current state of the art, the existing international standards and the current state of the technology. The relevance and viability of these requirements were validated by RENIEC (Spanish acronym of National Registry of Identification and Civil Status) specialist personnel through an inter institutional cooperation agreement between RENIEC and PNICP (Spanish acronym of National Program of Innovation for the Competitivity and Productivity).